Immune Status and Chemokine C Receptor 7 Expression in Primary in Patients with Immune Thrombocytopenia - Lin Zhang; Guo-zhong Zhou; Weiying Feng; Dan Li (Turkish Journal of Hematology, 2022)
Objective: The present study investigated immune disorders and chemokine C receptor 7 (CCR7) expression in primary immune thrombocytopenia (ITP) patients and analyzed their changes and clinical significance before and after treatments. Materials and Methods: Flow cytometry was used to detect the proportion of different immune cell subsets in the peripheral blood of 42 patients with ITP and 20 healthy controls at different time points. Treatments included first-line drugs, such as glucocorticoids and intravenous immunoglobulin, and second-line therapy, such as interleukin-11 and thrombopoietin receptor agonists. Results: An elevated CD4/CD8 ratio and decreased natural killer (NK) cells and CD4+CD25+CD127low regulatory T-cells (Tregs) were found in pretreatment ITP patients compared to healthy controls. The newly diagnosed group had a higher CD4/CD8 ratio and more NK cells than the relapsed group. Treg levels of the remission group were higher than those of the recurrence group. The CD4+CCR7+, CD8+CCR7+, and CCR7+ subsets of B cells and NK cells showed higher increases in the newly diagnosed and relapsed group compared to controls and the remission group. The values for the CD4+CCR7+ and CD8+CCR7+ subsets in the relapsed group were slightly higher than those in the newly diagnosed group. The CCR7+ subsets of CD4+ T-cells, CD8+ T-cells, NK cells, and B cells had lower values in the remission group compared to the relapsed group. Higher levels of the CD8+CCR7+ subset and lower levels of NK cells were found in the remission group compared to the controls. The ratio between the CD4+CCR7+ subset and CD8+CCR7+ subset was lower in ITP patients than in healthy controls. There was a negative correlation between the CD8+CCR7+ subset and platelet count in the ITP patients. Conclusion: ITP patients with CCR7 had immune disorders and high heterogeneity, and CCR7 was found to be involved in the pathogenesis of ITP. Further studies are needed to investigate effective treatments for ITP by targeted regulation of CCR7.